Pengaruh Kredibilitas Influencer dan e-WOM (Electronic Word of Mouth) Terhadap Minat Beli Produk Kecantikan Lokal Azarine Cosmetic - Haya Tsamarah Hanin; Citra Savitri; Syifa Pramudita Faddila (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The high number of Instagram users in Indonesia makes companies work with influencers to reach a wider audience, one of which is the beauty brand Azarine Cosmetic. Influencers are one of the factors contributing to increased product sales and forming positive e-WOM. This study aims to investigate how the role of influencer credibility and electronic word of mouth in increasing interest in buying local beauty products Azarine Cosmetic in Karawang. This research used quantitative approach and the data was analyzed by SEM-PLS. Followers of the @azarinecosmeticofficial Instagram account became the population and non-probability sampling techniques were used to sample 384 respondents. Data collection through questionnaires with google form and the use of SmartPLS 4 software to analyze data. The findings prove that the influencer credibility variable on e-WOM influences positively and significantly the e-WOM variable as well as influencer credibility influences positively and significantly in encouraging consumer interest in buying Azarine Cosmetic cosmetic products.